Industrial Engineering, Operations Management and Sustainability: Overview - Machado, Carla Gonçalves; Da Costa, Sérgio Eduardo Gouvea; Manfrim, Pamela Mocelin; De Lima, Edson Pinheiro (Brazilian Journal of Operations & Production Management, 2013)
the field of Industrial Engineering (IE), particularly those related to Operations Management (OM), with special regard to sustainability. Bibliometric analyses were performed by using information collected from 495 selected papers in nine OM-related international databases, based on the keywords “Sustainability” and “Operations Management”. Results pointed out to the evolution of the subject over the past two decades, the relationship among authors in their network of research, its effect on productivity and the related research topics. The results also indicated the main developing issues, authors, institutions and journals most devoted to the subject and the contribution of the study by establishing OM as a discipline in Industrial Engineering. Finally, the current paper will offer an overview of the trends for further research on sustainability into the OM field.